Acute multidimensional poverty : a new index for developing countries - Alkire, S; Santos, E (Oxford Poverty & Human Development Initiative (OPHI), 2010)
This paper presents a new Multidimensional Poverty Index (MPI) for 104 developing countries. It is the first time multidimensional poverty is estimated using micro datasets (household surveys) for such a large number of countries which cover about 78 percent of the world's population. The MPI has the mathematical structure of one of the Alkire and Foster poverty multidimensional measures and it is composed of ten indicators corresponding to same three dimensions as the Human Development Index: Education, Health and Standard of Living. The MPI captures a set of direct deprivations that batter a person at the same time. This tool could be used to target the poorest, track the Millennium Development Goals, and design policies that directly address the interlocking deprivations poor people experience. This paper presents the methodology and components in the MPI, describes main results, and shares basic robustness tests.